Impact of sugar-sweetened beverage taxes on price, import and sale volumes in an island: interrupted time series analysis. Issue 7 (18th May 2021) - Teng, Andrea M; Genç, Murat; Herman, Josephine; Signal, Louise; Areai, Danny; Wilson, Nick
Abstract: Objective: To evaluate the impact of changes in import tariffs on sweetened beverages. Design: Interrupted time series analysis was used to examine sweetened beverage tariff increases of 40–60 % in 2008 and to 75 % in 2012, and an approximately 11 % decrease in 2014 when an excise tax replaced the tariff. Post-tax trends were compared with a counterfactual modelled on the pre-tax trend for: quarterly price of an indicator beverage, monthly beverage import volumes (both 2001–2017) and quarterly sales volumes (2012–2017). In a controlled analysis, taxed beverage imports were compared with a sugary snacks control. Setting: Cook Islands. Participants: NA. Results: In the first year, after the 2008 tariff increase the price of the selected indicator soft drink increased by 7·3 % (95 % CI 6·3 %, 8·3 %) but after the 2012 tariff increase it decreased by 13·9 % (95 % CI –14·9 %, –12·8 %). At the same time, the import volumes of taxed beverages decreased by 13·2 % (95 % CI –38·1 %, 17·8 %) and 2·9 % (95 % CI –41·6 %, 72·5 %), respectively, and decreased by 24·8 % (95 % CI –36·9, –9·8) and 10·2 % (95 % CI –37·1, 37·5) in the controlled analysis. After the 2014 tax decrease, the price of the indicator soft drink decreased by 23·6 % (95 % CI –26·0 %, –21·1 %), sweetened beverage imports increased by 4·5 % (95 % CI –39·5 %, 156·0 %) and sales of full-sugar soft drinks increased by 31 % (95 % CI –21 %, 243 %). Conclusions: The increased import tariffs on sweetened beverages appeared to be effective for reducing import volumes, but this was partly reversed by the reduced tax/tariff in 2014.